Prevalence and predictors of smoking cessation among smokers receiving smoking cessation intervention in primary care in Qatar: a 6-month follow-up study - Al-Dahshan, Ayman; Al Muraikhi, Hissa; Musa, Sarah; Joudeh, Anwar; Al Baker, Wadha; Selim, Nagah; Bougmiza, Iheb (Frontiers in Public Health, 2023)
Objective To estimate the rate and predictors of smoking cessation in smokers attending smoking cessation clinics in primary care settings in Qatar. Methods A cross-sectional study was conducted among 759 smokers who had attended any of the 10 smoking cessation clinics in primary health care centers from January 2019 to June 2020. The sociodemographic, clinical, and smoking-related variables were assessed. Tailored behavioral and pharmacotherapy were delivered, and patients were interviewed at 6 months to estimate the 30-day point prevalence abstinence. To identify independent factors associated with smoking cessation, a multivariable logistic regression analysis was performed. Results The mean age of participants was 40.6 (±11.3), majority being married, Arab and employed, and having a tertiary education. Almost half of the smokers (48.7%) received varenicline alone, 42.6% received NRT, and 31.8% received a combination of both. The selection of drug therapy was based on preferences, experiences, and history of previously encountered adverse effects. The overall 30-day quit rate at 6 months follow-up was 32.4%. About three-quarters (72.5%) of participants had at least one quit attempt and 12.5% had 3 or more attempts. Later age at smoking initiation, lower cigarette consumption at baseline, lower CO concentration at baseline, use of smoking cessation pharmacotherapy, having made fewer quit attempts and non-exposure to secondhand smoke among friends were identified as significant predictors of successful quitting at 6 months. Conclusion The 30-day quit rate at 6 months follow-up (32.4%) is comparable to the worldwide figure. However, further efforts should be made to plan cost-effective tobacco dependence treatment taking into account predictors and at-risk groups.